The COVID-19 Pandemic and Its Impact on Socioeconomic Inequality in Psychological Distress in the UK: An Update - Xiaoying Gao; Apostolos Davillas; Andrew M. Jones (Institute of Labor Economics (IZA), 2021)
This paper extends the earlier work of Davillas and Jones (2021) on socioeconomic inequality in mental health, measured by the General Health Questionnaire (GHQ), to include the second national lockdown up to March 2021.
Keywords: C1; D63; I12; I14; 330; GHQ; health equity; socioeconomic inequality; COVID-19; mental health; psychological distress